(untitled) (Global Journal of Medical Research, 2022)
Choline is an essential nutrient in the poultry diet It plays a vital role in the metabolism and mobilization of accumulated abdominal fat In layer birds it helps in improving the rate of egg production egg quality and prevents fatty liver syndrome However synthetic choline has lots of demerits that need to be addressed To mitigate the drawbacks of choline the present study was conducted to evaluate the impact of Kolin PlusTM a polyherbal formulation POH manufactured by M s Natural Remedies Pvt Ltd Bengaluru India on the performance of the White Leghorn WL layer poultry birds In the current trial WL layer hens at the age of 41 to 55 weeks were distributed into 7 G1 to G7 study groups having 6 replicates 20 birds replicate per group All groups G2 to G7 except the normal control group G1 were supplied with high energy diet HED